Indonesia's Zakat Transformation in the Digital Era: Opportunities and Challenges - Sugeng, Anggoro; Triwibowo, Ananto; Saputra, Edi; Muhaimin Yusof, Ku Abdul (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: In the ever-evolving digital era, the transformation of zakat is becoming increasingly relevant and urgent. By utilizing digital technology wisely, zakat institutions can open the door to greater efficiency in the collection, management, and distribution of zakat, as well as increase community engagement in the practice of sharing blessings. However, to reach its full potential, there needs to be a concerted effort from all parties to overcome the challenges associated with using technology in religious and social contexts. Methodology: This research uses a qualitative descriptive approach combined with document analysis. This qualitative descriptive method focuses on explaining facts and circumstances that were observed during the research on Zakat Transformation in the Digital Era: Opportunities and Challenges. Findings: The results of this study show that the transformation of zakat in the digital era is a significant change in how zakat is managed and distributed by utilizing information and communication technology. Zakat institutions have five opportunities and four challenges of zakat transformation in the digital era, which should be prepared so that the transformation of zakat in this digital era positively impacts zakat institutions in particular and society in general.